The Function of Painting as a Visual Language (Djoko Pekik Trilogy Analysis) - Haryono, Haryono (Universitas 17 Agustus 1945 Surabaya, 2020)
Painting is a language expression that is expressed by artists through symbols or visual signs. Painting does not only reveal beauty, but also the role of symbolic language that will be realized by artists. The role of symbolic language in paintings is very influential to imply meaning, both denotation and connotation. Painting in general certainly aims to convey an unlimited message, it can be a social criticism, a historical record, and can also be present as an appeal. The message conveyed depends on what he wants to convey. So the focus of this study, how the role of painting as a visual language is realized through the symbols in the painting. This study uses the literature study method which is reviewed from some previous literature which is used as a sample or reference. The formation of visual language began in cave wall paintings, pictographs, and contemporary paintings such as the Djoko Pekik trilogy. Every painting shows that humans are able to express something through pictures or paintings.Keywords: Painting, Visual Language, Djoko Pekik Celeng Trilogy.